2009
DOI: 10.1038/jcbfm.2009.270
|View full text |Cite
|
Sign up to set email alerts
|

High-Affinity Dopamine D2/D3 PET Radioligands 18F-Fallypride and 11C-FLB457: A Comparison of Kinetics in Extrastriatal Regions Using a Multiple-Injection Protocol

Abstract: 18F-Fallypride and 11C-FLB457 are commonly used PET radioligands for imaging extrastriatal dopamine D2/D3 receptors, but differences in their in vivo kinetics may affect the sensitivity for measuring subtle changes in receptor binding. Focusing on regions of low binding, a direct comparison of the kinetics of 18F-fallypride and 11C-FLB457 was made using a MI protocol. Injection protocols were designed to estimate K1, k2, fND kon, Bmax, and koff in the midbrain and cortical regions of the rhesus monkey. 11C-FLB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 39 publications
4
76
0
Order By: Relevance
“…These authors argue and illustrate by simulation that in case of [ 11 C]FLB457 a higher plasma clearance and the observed lower k 2 and k off as well as the higher affinity contribute to its higher extent of specific cerebellar binding compared with FP. A relatively low proportion of lipophilic metabolites ( > 20% after 100 minutes) was reported both for FP and [ 11 C]FLB457, with little effect on parameter estimations (Vandehey et al, 2010). Congruently, for FP, the comparison of 2TCM and SRTM never revealed BP ND differences of much >15% as mentioned previously (Siessmeier et al, 2005;Slifstein et al, 2010).…”
Section: Discussionsupporting
confidence: 55%
“…These authors argue and illustrate by simulation that in case of [ 11 C]FLB457 a higher plasma clearance and the observed lower k 2 and k off as well as the higher affinity contribute to its higher extent of specific cerebellar binding compared with FP. A relatively low proportion of lipophilic metabolites ( > 20% after 100 minutes) was reported both for FP and [ 11 C]FLB457, with little effect on parameter estimations (Vandehey et al, 2010). Congruently, for FP, the comparison of 2TCM and SRTM never revealed BP ND differences of much >15% as mentioned previously (Siessmeier et al, 2005;Slifstein et al, 2010).…”
Section: Discussionsupporting
confidence: 55%
“…As seen in previous studies, sustained craving states suitable for use during long PET scans can be evoked by a multimodal combination of personalized cues, the manipulation of drug paraphernalia, and viewing realistic depictions of drug use. 12,30,38 Thus, participants developed an autobiographical script in which they described in detail a subjectively positive drug experience. Intranasal cocaine powder users were presented with a mirror, razor blade, straw, and bag of white powder (lactose).…”
Section: Methodsmentioning
confidence: 99%
“…36 The reference region was cerebellar grey matter based on the evidence that specific binding in this region is negligible with respect to other brain areas. 37,38 Regions of interest were defined on each individual's MRI scan in stereotaxic space, and BP ND values were derived for intergroup comparisons using Turku PET centre tools (turkupetcentre.net/; Appendix 1).…”
Section: Positron Emission Tomography Imagingmentioning
confidence: 99%
“…We reasoned that differences between patients with and without PG might be elevated when on pramipexole, since a single dose of 1 mg pramipexole has previously been shown to alter behaviour even in drug naïve individuals (Campbell-Meiklejohn et al, 2011). PET images were acquired using [11C] FLB-457, a high affinity marker used for assaying extrastriatal D2/D3 receptors (Farde et al, 1997), and which has been shown to be sensitive to endogenous DA levels in the PFC and midbrain (Montgomery et al, 2007;Narendran et al, 2009;Vandehey et al, 2010). PET scans were obtained with a high resolution PET CT, Siemens-Biograph HiRez XVI (Siemens Molecular Imaging, Knoxville, TN, U.S.A.) operating in 3D mode with an inplane resolution of approximately 4.6 mm full width at half-maximum.…”
Section: Scanning Proceduresmentioning
confidence: 99%